2013
DOI: 10.1002/oti.1350
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Reliability and Validity for “Make My Day” – A New Tool for Assessing Young Arab‐Israeli Children's Typical Daily Activities

Abstract: There is a paucity of literature regarding the daily routines of young children (4-7 years) and their perception of their performance. Research indicates that children's involvement in treatment therapy improves their self-consciousness, which contributes in return to the therapy's progress. Until recently, occupational therapists set goals for children by involving their parents in the planning. However, recent studies indicate that children are aware of their performance and can provide reliable data, given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…The results of the current systematic review also revealed that a number of child-report measures of occupational measures were validated with modest sample sizes and/or developed with small sample sizes (< 300 children). For example, the MMD was developed and validated using a total sample size of 62 children [ 8 ]. The other measure developed and/or validated with small sample sizes was the PEGS [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the current systematic review also revealed that a number of child-report measures of occupational measures were validated with modest sample sizes and/or developed with small sample sizes (< 300 children). For example, the MMD was developed and validated using a total sample size of 62 children [ 8 ]. The other measure developed and/or validated with small sample sizes was the PEGS [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Involving children in the intervention process has been shown to improve treatment outcomes [ 6 ]. Furthermore, children’s perceptions affect their quality of life, so collecting information from the child’s perspective is essential in clinical practice, in order to meet the aim of improving quality of life for the child [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Make My Day (MMD) (Ricon, Hen, & Keadan-Hardan, 2013) was designed to collect data regarding the activities comprising children's typical daily routines at home and at kindergarten (aged 5 to 6 years) or school (aged 6 to 7 years). It …”
Section: Children's Self-reports and Parental Reportsmentioning
confidence: 99%
“…Bununla birlikte çocukluk ve ergenlik dönemi boyunca eğitsel ve sosyal alanlarda başarılı olmak için gereklidir (Catroppa ve Anderson, 2006). Son yıllarda yapılan çalışmalarda çocukların günlük yaşamdaki performanslarının farkında olduklarını ve gelişim aşamasına uyarlanmış bir değerlendirmenin de onlar hakkında güvenilir veri sağlayabileceğini göstermiştir (Ricon, Hen ve Keadan-Hardan, 2013).…”
Section: Sonuç Tartışma Ve öNerilerunclassified